Effectiveness of Finger Hand Relaxation and Progressive Muscle Relaxation Techniques on Anxiety in Pre-Operative Sectio Caesarea Patients - Wiwik Widiyawati; Lingga Kusuma Wardani; Fajar Rinawati; Berlina Widyastuti; Nur Yeny Hidajaturrokhmah; Heri Saputro (Universitas STRADA Indonesia, 2024)
Background: Anxiety is a common thing that occurs in patients who will undergo surgery. The anxiety that occurs in preoperative patients can be felt from the time they are scheduled for surgery until the time of surgery arrives. Anxiety management can be done using pharmacological and non-pharmacological therapy. Purpose: The aim of this research is to analyze the effectiveness of finger grip relaxation techniques and progressive muscle relaxation on anxiety in pre-caesarean section surgery patients in the Kediri Regency Regional General Hospital. Method: This study used a Quasy-experiment With Pretest Posttest to determine the effect of finger grip and progressive muscle relaxation techniques. The sample selection in this study used a purposive sampling technique and a total of 56 patients were obtained who were divided into 2 groups, namely the finger grip intervention group and the progressive muscle intervention group. The pretest and posttest data for each group were then analyzed using the Wilcoxon Test to determine the effect and the Mann-Whitney Test to compare the posttest results of the 2 groups. Results: The results of the study showed that the Wilcoxon test in both intervention groups obtained a p-value < α (0.05), which means that before and after the intervention, both progressive muscle relaxation and finger grip relaxation had an influence on the anxiety level of pre-caesarean section patients. For the results of the Mann-Whitney test, the p-value was 0.063 or p-value > α (0.05), which means there was no significant difference between changes in anxiety whether those given progressive muscle relaxation intervention or finger grip relaxation. Conclusion: Finger grip relaxation techniques and progressive muscle relaxation techniques are both effective in reducing anxiety levels in pre-caesarean section surgery patients. So this non- pharmacological therapy can be an option for patients in dealing with anxiety problems before caesarean section surgery.